2022
DOI: 10.1093/mnras/stac103
|View full text |Cite
|
Sign up to set email alerts
|

BASS XXXI: Outflow scaling relations in low redshift X-ray AGN host galaxies with MUSE

Abstract: Ionised gas kinematics provide crucial evidence of the impact that active galactic nuclei (AGN) have in regulating star formation in their host galaxies. Although the presence of outflows in AGN host galaxies has been firmly established, the calculation of outflow properties such as mass outflow rates and kinetic energy remains challenging. We present the [$\rm O\, {\rm \small III}$]λ5007 ionised gas outflow properties of 22 z<0.1 X-ray AGN, derived from the BAT AGN Spectroscopic Survey using MUSE/VLT. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 168 publications
(233 reference statements)
3
36
1
Order By: Relevance
“…While there has been much tantalizing evidence of multiphase outflows in AGNs reported in the literature (e.g., Cicone et al 2014;Feruglio et al 2015;Karouzos et al 2016;Morganti 2017;Cicone et al 2018;Fluetsch et al 2019;Veilleux et al 2020), we have a poor understanding of how efficiently the outflows actually affect the host galaxy (e.g., Harrison et al 2018;Kakkad et al 2022). The naive expectation that AGN feedback expels and depletes the cold gas reservoir is certainly not borne out by much of the evidence.…”
Section: Summary and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…While there has been much tantalizing evidence of multiphase outflows in AGNs reported in the literature (e.g., Cicone et al 2014;Feruglio et al 2015;Karouzos et al 2016;Morganti 2017;Cicone et al 2018;Fluetsch et al 2019;Veilleux et al 2020), we have a poor understanding of how efficiently the outflows actually affect the host galaxy (e.g., Harrison et al 2018;Kakkad et al 2022). The naive expectation that AGN feedback expels and depletes the cold gas reservoir is certainly not borne out by much of the evidence.…”
Section: Summary and Discussionmentioning
confidence: 97%
“…Theoretical arguments abound concerning the need for negative AGN feedback to solve a suite of otherwise intractable problems in galaxy evolution. Theoretical and numerical works argue that outflows with kinetic powers of a few percent of the energy radiated by the AGN (  E L 0.05 0.5 Shimizu et al 2019;Kakkad et al 2022). A major source of uncertainty pertains to the degree to which outflows actually couple to the cold gas reservoir of the host galaxy.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This includes data in the radio (Baek et al 2019;Smith et al 2020), millimeter (Koss et al 2021;Kawamuro et al 2022), infrared (Ichikawa et al 2017;Lamperti et al 2017;Ichikawa et al 2019;den Brok et al 2022;Ricci et al 2022), optical (Koss et al 2017), and X-rays (Ricci et al 2017b). This has led to a number of follow-up studies comparing the X-ray continuum and optical properties of AGNs with their accretion rates (Oh et al 2017;Trakhtenbrot et al 2017;Ricci et al 2018;Rojas et al 2020;Kakkad et al 2022). The first BASS data release (Koss et al 2017) reported black hole masses for 473 AGNs, and X-ray properties for all 838 AGNs from the flux-limited Swift/BAT 70 month sample (Ricci et al 2017b).…”
Section: Samplementioning
confidence: 99%
“…Significant effort is being devoted to understanding the physics of AGN-driven outflows and measuring their energetic impact (e.g., Fischer et al 2018;Baron & Netzer 2019a, 2019bFörster Schreiber et al 2019;Mingozzi et al 2019;Davies et al 2020b;Wylezalek et al 2020;Avery et al 2021;Fluetsch et al 2021;Lamperti et al 2021;Luo et al 2021;Negus et al 2021;Ruschel-Dutra et al 2021;Speranza et al 2021;Vayner et al 2021;Bianchin et al 2022;Deconto-Machado et al 2022;Kakkad et al 2022). However, outflows are inhomogeneous, with a large range of densities and geometries, such that the derived gas masses and outflow rates depend strongly on how the gas densities are estimated.…”
Section: Feedback From Mass Outflows In Active Galaxiesmentioning
confidence: 99%